Mewujudkan Wisata Spiritual di Desa Adat Gelgel, Klungkung: Berbasis Website - I Made Mardika; Agus Kurniawan; I Putu Yudi Prabhadika; Ni Made Jaya Senastri (Universitas Warmadewa, 2023)
Realizing Spiritual Tourism in the Gelgel Traditional Village Klungkung regency requires website-based tourism packaging and promotion. The aim is to empower the community in developing Spiritual Tourism through Information Technology. Three forms of activity are programmed, namely: creating tourist information, packaging content, and promoting spiritual tourism online. The solving method is carried out through: (1) Assistance in the preparation of temple cultural heritage information content as spiritual tourism on the website, (2) Assistance in structuring the potential of temple cultural heritage to be packaged into Spiritual tourist attractions, and (3) branding assistance and promoting